TEACHERS’ FAMILIARITY ON HIGH ORDER THINKING SKILLS IN SCIENCE CLASSROOM OF SECONDARY SCHOOL - Hasna Muhandisah; Erman Erman; Dhita Ayu Permata Sari (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
High Order Thinking Skills (HOTS) is a student’s thinking process at a higher cognitive level from various concepts and methods in the learning taxonomy. HOTS learning can improve student thinking skills at a higher level. Teachers have a very important role in making students skilled in solving problems so that they are required to be able to apply learning that can train students to think at higher levels (HOTS). This study aims to know high order thinking skills of Muhammdiyah Junior High School student in science learning. Participants in this study were 58 students from Muhammadiyah Junior High Schools in Jombang Regency. This study used a descriptive qualitative research with test of LOTS and HOTS. The results of the data show that students are able to work on HOTS questions only up to the analysis, namely C4. However, students are already good at working on C1, C2 and C4 questions with a percentage above 70%, it is high. Students have not been able to think at high levels at stages C5 and C6 because the teacher rarely teaches and asks questions at the application and development.